2019
DOI: 10.1155/2019/8159567
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Characterization of Salmonella Isolated from Large-Scale Breeder Farms in Shandong Province, China

Abstract: This study aimed to investigate the prevalence and antimicrobial resistance of Salmonella spp. isolated from large-scale breeder farms in Shandong Province, China. A total of 63 Salmonella isolates (63/409, 15.4%) were identified from 409 samples collected from five large-scale breeder farms in Shandong Province. These Salmonella isolates were assayed for serotype, antimicrobial susceptibility, prevalence of class 1 integrons, quinolone resistance genes, and β-lactamase genes and subtyped by multilocus sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 23 publications
2
19
1
Order By: Relevance
“…Among three chicken breeds (Luhua, Langya and Qingjiaoma) fed on antibiotic-free diets and one conventional Bairi chicken, different serotypes and ST types of Salmonella were identified. However, the dominating serotype among these breeder flocks in this study was S. Pullorum, which was significantly different from the prevalent isolates (100% S. Enteritidis) from fecal swabs and chicken embryos of large-scale breeder farms in China (19). Zhao et al (27) investigated the prevalence and characteristics of Salmonella in free-range chickens in China and showed that a total of 38 Salmonella isolates (38/300, 12.7%) were recovered and the most common serotype was S. Enteritidis (81.6%).…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…Among three chicken breeds (Luhua, Langya and Qingjiaoma) fed on antibiotic-free diets and one conventional Bairi chicken, different serotypes and ST types of Salmonella were identified. However, the dominating serotype among these breeder flocks in this study was S. Pullorum, which was significantly different from the prevalent isolates (100% S. Enteritidis) from fecal swabs and chicken embryos of large-scale breeder farms in China (19). Zhao et al (27) investigated the prevalence and characteristics of Salmonella in free-range chickens in China and showed that a total of 38 Salmonella isolates (38/300, 12.7%) were recovered and the most common serotype was S. Enteritidis (81.6%).…”
Section: Discussioncontrasting
confidence: 62%
“…Among the 14 antibiotics used in this study, the resistance rates of all Salmonella isolates to 11 antibiotics in conventional chicken were higher than those from chickens fed on antibiotic-free diets. The average MDR rate (20.2%, 22/109) of Salmonella isolates from chickens fed on antibiotic-free diets was significantly lower than the rates of 100% among 63 isolates examined by Yang et al (19) from conventional farms in a similar geographical region, and also lower than that from other poultry farms in China (43). These data indicated that the use of antibiotics may promote the development of MDR Salmonella (44).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In this study, both MLST and PFGE subtyping grouped isolates together into the representing serovar. All 55 Enteritidis isolates were assigned into ST11, a vastly distributed clone across the world [14,30,31]. However, PFGE analysis showed that the 55 isolates displayed nine banding patterns distinguishable by at least one band difference ( Figure 2); this banding pattern similarity was higher than that of S. Enteritidis isolates from breeder chickens reported recently [32].…”
Section: Discussionmentioning
confidence: 91%
“…Poultry can become infected with different Salmonella serotypes with high morbidity and mortality during the first three weeks of their life, and may also become carriers which can disseminate bacteria spread horizontally within flocks, or vertically to progeny via contaminating breeding eggs, leading to embryo mortality or rapid death of newly hatched birds. The prevalence of Salmonella infection in Chinese poultry farms has been widely described [13,14]. In the chicken sector, voluntary control in breeding flocks in combination with national statutory elimination of S. Pullorum has reduced Salmonella infection.…”
Section: Introductionmentioning
confidence: 99%